Non-HDL Cholesterol Versus LDL Cholesterol as a CVD Risk Factor in Diabetic Subjects (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Objective: Serum low density lipoprotein (LDL) cholesterol is considered as the primary target of lipid lowering therapy and non-high density lipoprotein (HDL) cholesterol is the recommended second target. Recent studies claimed that non-HDL cholesterol is a better predictor of cardiovascular diseases (CVD) than LDL cholesterol. In this study we aimed to compare non-HDL cholesterol and LDL cholesterol as a CVD risk factor in confirmed diabetic subjects. Materials and methods: In this cross-sectional observational study, 1042 confirmed diabetic subjects selected randomly were included. HbA1cResults: In the total subjects, 767 (74%) subjects had LDL cholesterol > 100 mg/dL and 822 (79%) subjects had non- HDL cholesterol > 130 mg/dL. HbA1c values were different (p